The construction of test reliability statistical criteria by a computer simulation - Navickienė, Olga; Krylovas, Aleksandras; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2013)
The paper describes a computer simulation experiment of knowledge assessment test when item’s characteristic functions are power functions and knowledge level of the population has uniform or normal distribution. The inversions of the conditional means were calculated and probability distributions of the numbers of inversions were simulated. In practice of construction of knowledge tests for checking their suitability (validity) observed values of inversions are compared with reference values obtained byMonte Carlo experiments.